The effect of environmental, social and governance criteria on the corporate value of listed companies in Malaysia - Shahrun, Nur Shahira Bte; Ramasamy, Suganthi; Yen, Yuen Yee (Asian Economic and Financial Review, 2023)
Environmental, social, and governance (ESG) criteria are used by most corporations to achieve and maintain the best management quality. Thus, implementing ESG might assist firms in Malaysia to improve their corporate performance. The purpose of this research is to analyze the effect of ESG on corporate performance in terms of the value of Malaysian listed firms. A total of 45 companies listed on Bursa Malaysia that have complete ESG data from 2011–2021 were selected from Bloomberg’s ESG database. Corporate value was measured using three indicators – return on assets (ROA), return on equity (ROE) and Tobin’s Q. According to the results, the ESG scores have an insignificant positive influence on ROE and Tobin’s Q. However, the ESG scores have a negative but insignificant impact on ROA. The individual Environmental score has a negative impact on ROA but a positive impact on ROE and Tobin’s Q. Meanwhile, Social on its own has an insignificant negative impact on all variables, and Governance has a positive but insignificant impact on all variables. Based on the inconsistencies between the results of this study and those of previous research, the conclusions on whether ESG criteria promote business value and performance cannot be reached. ESG practices have become increasingly important, not only for policymakers but for governments and stakeholders. Hence, the outcome of this study will be useful for the government to reduce costs and implement policies to improve corporate performance in Malaysia.